MODEL SISTEM ANTRIAN UINSA MART MENGGUNAKAN POLA SINGLE CHANNEL SINGLE PHASE - Choirun Nisa, Nila; Wahyu, Alfian; Samudra, Aryo; Fatoni, Rizal (Universitas Sangga Buana, 2024)
Simulation and modeling using a single channel single phase aims to optimize the cashier queuing system at Uinsa Mart. Queuing is a common phenomenon in everyday life where customers have to wait to get service. Delays in queues can affect the customer experience. This method uses literature studies, field studies, system implementation, and provides solutions. Observations were made to collect data regarding arrival time, service time, and other related variables. The data is processed and used as input to create a simulation model using Anylogic software. Queuing can be applied in the context of a canteen and provides recommendations for improving the queuing system at Uinsa Mart. Provides information about the observed queuing system, as well as the queuing model simulation that has been implemented. Provides further understanding of queuing system optimization and its application in the canteen context.